Representasi hegemoni kultural gramsci dalam film tuhan, izinkan aku berdosa (kajian semiotika roland barthes) - Jumardan, Sulis (Maliki Interdisciplinary Journal, 2025)
This study analyzes Kiran’s struggle in exposing the corruption of those around her, using Roland Barthes’ semiotic theory and Antonio Gramsci’s concept of hegemony. Through a qualitative approach, the research reveals how signs and myths created by the ruling elites function to maintain their hegemony in society. Data were obtained through narrative and symbolic analysis of social interactions, campaign media, and Kiran’s acts of resistance. The findings show that people around Kiran employed hegemonic narratives through symbols of power and myths of virtue to manipulate public perception. However, Kiran succeeded in deconstructing these myths, exposing the corruption behind the idealized image constructed by the authorities. The discussion highlights that although hegemony is difficult to resist, Kiran’s critical actions created cracks within such symbolic domination. This study concludes that semiotic and hegemonic analysis can serve as effective tools for understanding the dynamics of power and resistance in the context of local politics.